Akidah dan Syariat: Simfoni Ilahi dalam Tatanan Hidup Muslim - Elvy Gustina; Arman Husni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the integral relationship between aqidah (faith) and sharia (Islamic law) in Islam as a unified system that governs a Muslim's way of life. Aqidah serves as the foundation of belief, while sharia represents the practical implementation of that faith across all aspects of life. The disintegration between these two elements has led to various negative social phenomena, including hypocrisy, secularism, and moral decline. Using a qualitative approach and library research method, this study deeply examines primary Islamic sources such as the Qur'an, Hadith, classical texts, and contemporary Islamic thought. The findings reveal that integrating aqidah and sharia education is an urgent necessity within Islamic educational systems, aiming to shape a generation of Muslims who possess a comprehensive understanding of faith and consistently practice Islamic teachings. This integrated educational model is essential for developing individuals with strong character, rooted in faith, and capable of facing contemporary challenges while adhering to divine values.